The Gender Differential Analysis: Knowledge, Attitude, Practices and Aspirations of Pesticide Use Among Cocoa Farmers In Asamankese Cocoa District, Ghana - Acheampong, Angela Otiwaa; Tham-Agyekum, Enoch Kwame; Ankuyi, Fred; Bakang, John-Eudes Andivi; Okorley, Ernest Laryea; Aidoo, Danley Colecraft; Jones, Ebenezer Osei (Food, Agriculture and Natural Resources - NETWORKS, 2023)
Attempts to attain flawless agricultural production are still hampered by a range of restrictive factors including water scarcity, climate change, plant pests and diseases. Worries about the negative and unpleasant repercussions of pesticides on health are evolving in developing countries including Ghana. Cocoa farmers’ knowledge awareness, attitude, practices and skills in handling pesticides and the potential hazards it poses to them are vital in preventing pesticide exposure and hazards. This study examines the knowledge, attitudes, practices and aspiration of cocoa farmers in Ghana regarding pesticide use and the potential hazards it poses to their health. The paper highlights the importance of understanding the diverse roles and perspectives of male and female farmers in agricultural production. The study uses a quantitative approach and a cross-sectional descriptive approach to analyze data from 364 cocoa farmers in the Asamankese Cocoa District. The study found that both male and female cocoa farmers have a positive attitude towards pesticide usage, and their knowledge of pesticide handling practices is adequate. The study also found that male and female farmers have different levels of knowledge, attitudes, and practices regarding pesticide use. The findings suggest that there is a need for increased awareness and education on safe pesticide handling practices to prevent pesticide exposure and its negative health effects on farmers.